Oral Lipoma - A Case Report - Parita Chitroda; Jigna Shah (Wolters Kluwer Medknow Publications, 2003)
Lipoma is a benign, slowly growing encapsulated neoplasm, composed of matured fat cells that occurs with relatively rare frequency in oral cavity. According to the reported cases, the involved sites in order of frequency are buccal mucosa, tongue, floor of the mouth, huccal sulcus & vestibule, lips, palate & gingiva. Clinically, it appears as a pedunculated or sessile and usually as a solitary tumor with overlying mucosa normal. Its consistency varies from soft to firm and in some cases so firm that pseudofluctuancy can be elicited. Histologically it is composed predominantly of matured adipocytes admixed with collagenic streaks and is often well demarcated from surrounding tissue. A case of Lipoma of left buccal vestibule is presented in a 40 years male patient. Clinically, it was presented with a painless, dome shaped, small swelling with normal overlying mucosa. Fluctuation was elicited in this case. The lesion was completely excised under local anesthesia and histopathological examination was done. Thus a case of oral lipoma involving buccal vestibule is presented which can be included as a rare possibility in the differential diagnosis of various swellings of buccal vestibule.